Experiments and evaluation on residual strength of X52 steel pipe with various internal defects - Qi, Changchao; Li, Tang; Liu, Chang; Gao, Jian; Du, Xinjie; Ren, Qingyang; Jia, Wenlong (Frontiers in Energy Research, 2023)
The strength of the natural gas transmission pipe is reduced due to sag deformation and corrosion defects. However, there are rare experiment data to quantitatively describe the effect of the defect’s size and position on the pipe strength. This paper designed seven groups of steel pipes with various defects to perform the hydrostatic bursting experiments, and to research the effects of the defects on the strength of the steel pipe. The experimental pipe sample is selected as the X52 material. Three types of defects were set up: concave and corrosion combinational defects, one corrosion defect, and two corrosion defects. The pipe rupture size, the strain around defects, and pipe perimeters before and after experiments are measured, finally yielding the strain-pressure curve of each steel pipe. Comparisons of experimental results show that the defect depth is the dominant factor affecting the pipe strength. Moreover, results show that the DNV-RP-F101 code tends to yield less distance beyond which two defects will not affect each other. The ASME B31G code also tends to give a lower residual strength of the pipe. However, in comparison with the PCORRC criterion, the ASME B31G formula has higher accuracy for X52 pipes. The average relative deviation between the experimental and calculated corroded pipe strength is 14.87%.